PWE-138 Treatment Of Patients with Chronic Hepatitis C Genotype 1 and Advanced Fibrosis with Protease Inhibitors- Il28B Discordance Results in Early Viral Decline but Late Relapse. (4th June 2013) - Tanwar, S; Trembling, P M; Hogan, B J; Catt, J; Glasgow, S; Glover, N; Ju, M; Hains, M; Moore, M T; Velazquez, C; Conibear, T; Labbett, W; et al.
Abstract : Introduction: We report the impact of host and viral factors on treatment outcome in the first 53 patients who have completed therapy for CHC with either telaprevir or boceprevir, in combination with pegylated-interferon and ribavirin (PEG/R) at our centre. Methods: Patients were treatment naïve or experienced with F3 or F4 fibrosis, CHC genotype1 and HCV RNA > 10, 000 IU/ml. Data were collected on host and viral factors including single nucleotide polymorphisms (SNPs) in the IL28B gene noncoding region at sites rs12979860 and rs8099917. Results: 53 patients (42 Caucasian, 32 F4) were treated with TVR (n = 41) and BOC (n = 12). Seven patients were treatment naïve. Subtyping was unattainable in 2 patients. Thus far, 18 patients (34%) have failed treatment and the remainder are being evaluated for SVR (24 patients with SVR-4 to date). HCV viral negativity at triple therapy week 4 was associated with treatment success in patients with rs12979860CC and rs8099917TT and rs12979860non-CC and rs8099917non-TT (OR 20.2 P-value < 0.001) but not in patients with discordance between the two IL28B polymorphisms (rs12979860non-CC and rs8099917TT, P-value = NS). Despite 86% HCV RNA negativity at triple therapy week 4, patients with discordant IL28B genotype results demonstrated a failure rate of 43% predominantly due to virologic breakthrough during PEG/R. In addition, all patients who ultimately failed therapy after attaining eRVR and qualifying for shortened therapy had IL28B genotype discordance. Multivariate logistic regression identified that HCV negativity at triple therapy week 4 (p-value < 0.001), rs12979860 (p-value = 0.02) and rs8099917 (p-value = 0.001) were all independent predictors of treatment outcome after accounting for the remaining factors as potential confounders. Conclusion: In our prospective cohort of CHC patients with advanced fibrosis treated with PIs, HCV RNA negativity at triple therapy week 4 and both IL28B genotypes were independent predictors of treatment outcome. Despite similar rates of early viral suppression, our preliminary data indicate more favourable end of treatment results for rs12979860CC and rs8099917TT versus rs12979860non-CC and rs8099917TT. Disclosure of Interest: None Declared.